KONSTRUKSI PENGAMPUNAN PAJAK PAJAK PENGHASILAN (PPh) Pasal 23 DI INDONESIA - Tjoa, Robby; Yohanes, Yohanes; Tajib, Eddy (Fakultas Hukum Universitas Narotama, 2026)
Tax plays a crucial role as a primary instrument in supporting national development, serving as one of the main pillars of state revenue. Among the various tax instruments, Income Tax (PPh), particularly Article 23 (PPh 23), holds significant importance because it governs the withholding of tax on income derived from capital, services, rent, and certain types of rewards or appreciation. The implementation of PPh 23 is intended to ensure fairness, expand the tax base, and prevent tax evasion through third-party withholding mechanisms. However, in practice, challenges remain regarding the effectiveness and compliance of PPh 23, especially due to differing interpretations of taxable objects and the lack of awareness among taxpayers. To address these issues, the tax amnesty policy has emerged as an essential fiscal instrument aimed at improving voluntary compliance, expanding the taxpayer database, and strengthening the legal construction of PPh 23. Indonesia has previously implemented this policy through Law Number 11 of 2016 concerning Tax Amnesty, which provided an opportunity for taxpayers to disclose unreported assets with the promise of certain benefits and legal certainty. This study employs a normative legal research method with a statutory and conceptual approach to analyze the regulatory framework of Income Tax Article 23 in relation to tax amnesty. The objective is to explore how tax amnesty contributes to enhancing taxpayer compliance and reinforcing the legal certainty of PPh 23 enforcement within Indonesia’s tax system. Keywords: Construction, Tax Amnesty, Income Tax Article 23